Detection of rodent-borne intestinal helminths infestation in North Sumatra, Indonesia: A potential public health concern - Hutagalung, Sunna Vyatra; Mardiani, Tengku Helvi; Albar, Marina Yusnita; Kurniawan, Ahadi; Sinaga, Ledy Afrida; Nasution, Hidayatullah; Hasibuan, Panusunan; Wardhana, April Hari (YCAB Publisher, 2024)
Background:Studies indicate that approximately 75% of emerging infections in humans are zoonotic, originating from animals. Within the One Health framework, it is evident that recent global environmental changes have contributed to the widespread proliferation of rodents, increasing their interaction with human dwellings and subsequently elevating the risk of rodent-borne diseases. Rodents play a crucial role in the transmission of zoonotic pathogens, including various intestinal helminths such as the cestodes Hymenolepis nanaand Hymenolepis diminuta. Objective:The objective of this study was to identify zoonotic intestinal helminths present in the rodent population of North Sumatra. Methods:This descriptive cross-sectional study utilized purposive sampling and was conducted in three regencies of North Sumatra: Serdang Bedagai, Batu Bara, and Asahan. Rodents were captured using baited traps placed both inside and outside residential areas. Following species identification, the rodents were euthanized, and their intestines were dissected. The intestinal contents were macroscopically examined for the presence of adult helminths, then processed using the formalin-ether concentration technique (FECT) and microscopically analyzed for helminths and their eggs. Results:A total of 47 rodents were captured, with Rattus tanezumibeing the most prevalent species (59.6%), followed by Rattus norvegicus(29.8%) and Rattus tiomanicus(4.3%). Other species identified included Rattus argentiventer, Rattus exulans, and Mus musculus, each constituting 2.1% of the total sample. Seven species of intestinal helminths were detected in 37 of the rodents (78.8%), with most animals having co-infections involving multiple helminth species. Notably, Mus musculusshowed no evidence of infection, whereas the remaining rodent species exhibited a high transmission rate of intestinal helminths, ranging from 71.4% to 100%. The helminths identified were Nippostrongylus brasiliensis(61.7%), Moniliformis moniliformis(36.2%), Heligmosomoides polygyrus(27.7%), and the cestode Hymenolepis nana(8.5%). Additionally, Ascarids, Trichuris spp., and Hymenolepis diminutawere also detected, each with a prevalence of 4.3%. Conclusion:This study identified seven species of intestinal helminths in rodents captured in selected areas of North Sumatra, predominantly from Rattus tanezumiand Rattus norvegicus. Some of the identified helminths, such as Hymenolepis nanaand Hymenolepis diminuta, are known zoonotic pathogens, highlighting the public health risks associated with rodent-borne diseases. Keywords:one health; zoonosis; rodents; infestation; helminths